The nomenclatural cases of Veronica steppacea and V. menthifolia (Plantaginaceae), with notes on the status of provisional names and type designation - Mosyakin, Sergei L.; Albach, Dirk C.; Daubert, Mareike; Antonenko, Svitlana I. (Phytotaxa, 2024)
A nomenclatural and taxonomic analysis is provided for the name Veronica steppacea Kotov (Plantaginaceae: Veronica subg. Pseudolysimachium) and some associated names of plants occurring mainly in the Steppe and Forest-Steppe physiographic zones of southeastern Europe, especially Ukraine. In particular, it is confirmed that the name V. steppacea was validly published in 1954. The first publication of that name in 1927 was invalid because it was published with “the mere mention of the subordinate taxa included in the taxon concerned” (Art. 36.2 of the ICN). Following the current provisions of the ICN, the specimen KW000058110 collected by Kotov in 1949 (“1948” in the protologue is a typo or error) in southeastern Ukraine (Donetsk Region, Volnovakha District, Starohnativka) is designated here as the lectotype of the name V. steppacea, one of three specimens at KW annotated by the author as “types” and belonging to one gathering. A list of main synonyms of V. steppacea (including V. borysthenica, V. cretacea, V. donetzica, V. tzvelevii, etc.) is provided. A corrected type designation is published for the name V. menthifolia H. Schott ex Roem. & Schult.: the illustration in Clusius (1601) is designated as the lectotype and the specimen from the herbarium of H. Schott (BP 348066) is designated as the epitype. Most probably V. menthifolia is conspecific with V. barrelieri (referring to an eastern Submediterranean European taxon), and thus the name V. steppacea should be used for related southeastern European plants. Several potential amendments of the ICN are briefly considered based on the nomenclatural cases discussed in the article.